Exercise stress test reveals ineligibility for subcutaneous implantable cardioverter defibrillator in patients with Brugada syndrome. (1st September 2017) - Tachibana, Motomi; Nishii, Nobuhiro; Morita, Hiroshi; Nakagawa, Koji; Watanabe, Atsuyuki; Nakamura, Kazufumi; Ito, Hiroshi
Abstract: Background: The eligibility of patients with Brugada syndrome (BrS) for implantation of a subcutaneous implantable cardioverter defibrillator (S‐ICD) is not well known. This study aimed to clarify the eligibility of BrS patients for S‐ICD using electrocardiography (ECG) at rest and during exercise testing. We also analyzed factors associated with ineligibility for S‐ICD from standard 12‐lead ECG at rest. Methods: We enrolled 110 consecutive BrS patients who visited Okayama university hospital from December 2015 to December 2016. All patients were assessed for S‐ICD eligibility, which required one lead to satisfy the S‐ICD screening template. We assessed standard 12‐lead ECG parameters in all participants. Of those who passed S‐ICD screening, 45 patients were assessed for S‐ICD eligibility during treadmill stress test. Results: Mean age of study patients was 54 ± 13 years and 108 (98%) were men. In total, 89 patients (81%) satisfied S‐ICD indications at rest. Existence of complete right bundle branch block (CRBBB) on standard 12‐lead ECG was a significant predictor of ineligibility for S‐ICD (odds ratio, 5.00; P   = 0.03; 95%CI, 1.14–21.98). Of the 45 patients who underwent treadmill stress testing, 11 patients (24%) showed ineligibility for S‐ICD during the test. Conclusion: CRBBB was a predictor of ineligibility for S‐ICD in patients with BrS. Sinus tachycardia changes ECG morphology in some patients and stress testing should be considered before S‐ICD implantation.